Electrochemical and Electronic Devices

By introducing a functional layer that can absorb the electrolyte into the battery electrode container and controlling its volume ratio to the active material layer, the problems of insufficient liquid retention of the battery and uneven release of the electrolyte are solved, and better circulation characteristics and appearance flatness are achieved.

JP2025510921APending Publication Date: 2025-04-15NINGDE AMPEREX TECHNOLOGY LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2024557218
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-03-31
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

During the use of existing secondary batteries, insufficient electrolytes will lead to poor cycle life. At the same time, the uneven release of excessive electrolytes in the outer packaging will lead to uneven surface of the battery, affecting appearance and energy density.

Method used

In the electrode container of the battery, a functional layer is introduced that can absorb the electrolyte and improve the liquid retention capacity of the battery by controlling the volume ratio of the functional layer to the active material layer (between 1% and 10%) to prevent uneven release of the electrolyte.

Benefits of technology

It effectively improves the circulation characteristics of the battery, prevents uneven surfaces of the battery, reduces the loss of energy density, and meets the requirements of battery appearance and transportation standards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025510921000001_ABST
    Figure 2025510921000001_ABST
Patent Text Reader

Abstract

An electrochemical device is provided that includes an electrode assembly, the electrode assembly including an electrode piece, the electrode piece including a current collector, the current collector including a first region and a second region, an active material layer is provided in the first region, a functional layer is provided in the second region, and when a volume ratio of the functional layer to the volume of the active material layer is R, R satisfies 1%≦R≦10%. The electrochemical device of the present invention has a high liquid retention capacity, a flat appearance, and good cycle characteristics. Also provided is an electronic device that includes the electrochemical device.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of energy storage, and in particular to electrochemical and electronic devices. [Background technology]

[0002] Secondary batteries (electrochemical devices) have the advantages of high energy density, good cycle characteristics, environmental friendliness, safety, and no memory effect, and are therefore widely used in fields such as portable electronic products, electric vehicles, and energy storage. However, with the development of science and technology, the demand for energy density and cycle life of secondary batteries is increasing. In secondary batteries, the amount of electrolyte added (liquid retention amount) is not only an important factor that affects the cycle life of the battery, but also an important factor that affects the appearance and shipping standards of the battery. If the amount of electrolyte added is insufficient, the consumption of electrolyte during the cycle process cannot be effectively compensated for, which is disadvantageous to the long cycle life of the battery, so it is necessary to inject extra electrolyte into the battery. However, the extra electrolyte is likely to be liberated unevenly inside the outer bag (e.g., aluminum plastic film), causing unevenness on the battery surface, and further causing poor appearance and loss of energy density of the battery. Improving the liquid retention amount of secondary batteries and effectively improving the expansion caused by the electrolyte of secondary batteries to meet the shipping appearance of secondary batteries are currently problems that need to be solved urgently. Summary of the Invention

[0003] In view of the above problems existing in the prior art, the present invention provides an electrochemical device and an electronic device including the electrochemical device, thereby increasing the liquid retention capacity of the electrochemical device, improving cycle characteristics, and also alleviating the problem of expansion of the external appearance due to the electrolyte.

[0004] In a first aspect, the present invention provides an electrochemical device, the electrochemical device includes an electrode assembly, the electrode assembly includes an electrode piece, the electrode piece includes a current collector, the current collector includes a first region and a second region, an active material layer is provided in the first region, a functional layer is provided in the second region, and when the volume ratio of the functional layer to the volume of the active material layer is R, R satisfies 1%≦R≦10%. The inventor of the present invention has found through research that the liquid retention amount of the electrochemical device can be improved and the cycle characteristics can be improved by coating a functional layer capable of absorbing an electrolyte on the current collector region where the active material of the electrode piece is not coated, and controlling the volume ratio of the functional layer to the volume of the active material layer within the above range. In addition, it is possible to prevent unevenness on the surface of the electrochemical device caused by excess electrolyte being unevenly liberated inside the exterior bag (e.g., aluminum plastic film), and further improve the flatness of the appearance of the electrochemical device, thereby reducing the loss of energy density. In some embodiments, the functional layer can absorb the electrolyte.

[0005] According to some embodiments of the present invention, the electrochemical device satisfies R≧k / (D×P), where D is the swelling degree of the functional layer, P is the porosity of the active material layer, and k satisfies 0.004≦k≦0.008. When the above relationship is satisfied, the electrochemical device has excellent cycle characteristics and low energy density loss at the same time.

[0006] According to some embodiments of the present invention, when the swelling degree of the functional layer is D, D satisfies 200%≦D≦800%. If the swelling degree of the functional layer is less than 200%, the electrolyte retention rate of the functional layer is low, which is disadvantageous for improving the appearance of the electrochemical device. If the swelling degree of the functional layer exceeds 800%, the stability of the functional layer itself is poor, and the membrane is easily removed during the cycle process, which further affects the effect of improving the appearance and the electrical performance of the subsequent cycles. In some embodiments, the swelling degree of the functional layer is 300% to 600%.

[0007] According to some embodiments of the present invention, when the porosity of the active material layer is P, P satisfies 5%≦P≦25%. The porosity of the active material layer determines the infiltration effect of the electrolyte, and when the porosity is within the above range, the absorption effect of the active material layer on the electrolyte is the highest. If the porosity is too high, the structure of the active material layer becomes unstable and the membrane is easily removed during cycling. If the porosity is too low, the absorption speed of the electrolyte is slow, which is likely to cause poor infiltration of the electrolyte, and the capacity decay during the charge and discharge process of the electrochemical device is accelerated.

[0008] According to some embodiments of the present invention, the functional layer comprises a polymer formed from at least one of acrylic acid monomers, acrylic ester monomers, and styrene monomers.

[0009] According to some embodiments of the present invention, the mass percentage of the polymer is 30% to 100% with respect to the mass of the functional layer.

[0010] According to some embodiments of the present invention, the functional layer further comprises inorganic particles, which can avoid failure caused by internal short circuit when the electrochemical device is penetrated by external force, and can effectively improve the safety performance of the electrochemical device in the penetration test.

[0011] According to some embodiments of the present invention, the inorganic particles include at least one of boehmite, diaspore, aluminum oxide, barium sulfate, calcium sulfate, and calcium silicate.

[0012] According to some embodiments of the present invention, the electrolyte retention rate of the functional layer is 40% to 120%.

[0013] According to some embodiments of the present invention, a non-destructive ultrasonic intelligent diagnostic system is used to measure, and ultrasonic waves are emitted to the electrochemical device along the thickness direction of the electrochemical device, and a signal feedback distribution map for the ultrasonic waves of the electrochemical device is obtained, and the proportion of the area of ​​the electrochemical device in the signal feedback distribution map where the ultrasonic signal intensity is 1333 mV or more is 30% to 95%. Ultrasonic waves are mechanical waves that need to propagate depending on the medium. When there is no electrolyte infiltration between the electrode materials, the propagation of ultrasonic waves is realized only by the direct contact between the electrode material particles, and the irregular particles cause the ultrasonic waves to generate a large amount of reflection and refraction, and the signal intensity is greatly attenuated. However, when the electrolyte can completely infiltrate the electrode material, the liquid environment provides a good propagation path for the ultrasonic waves, and a significant part of the ultrasonic waves is not interfered with by the particles, so that the signal intensity is ensured. Therefore, in the measurement of the non-destructive ultrasonic intelligent diagnostic system, the signal feedback intensity for the ultrasonic waves at each point of the electrochemical device can well characterize the distribution and infiltration situation of the electrolyte inside the electrochemical device, and the higher the proportion of the area with high signal intensity, the more uniform the distribution of the electrolyte inside the electrochemical device.

[0014] According to some embodiments of the present invention, the flatness of the electrochemical device is 0 to 0.5 mm.

[0015] According to some embodiments of the present invention, the electrode assembly is a wound electrode assembly, in which a second region is provided at a winding start end and a winding end end of the current collector, and a functional layer is provided in the second region at the winding end end.

[0016] In a second aspect, the present invention provides an electronic device comprising an electrochemical device of the first aspect.

[0017] The present invention can improve the liquid retention capacity of the electrochemical device and improve cycle characteristics by applying a functional layer to the current collector area where the active material of the pole piece is not applied and controlling the ratio of the volume of the functional layer to the volume of the active material layer within the range of 1% to 10%. In addition, it can prevent unevenness on the surface of the electrochemical device caused by uneven liberation of excess electrolyte inside the exterior bag (e.g., aluminum plastic film), improve the flatness of the appearance of the electrochemical device, and reduce loss of energy density. [Brief description of the drawings]

[0018] [Figure 1] 1 is a schematic diagram of an electrode strip in an electrochemical device according to some embodiments of the present invention, where: 1 - current collector; 2 - active material layer; 3 - functional layer. [Diagram 2] 2 is a schematic diagram of a wound electrode assembly in an electrochemical device according to some embodiments of the present invention, where: 1 - current collector; 2 - active material layer; 3 - functional layer; 4 - winding end; 5 - winding start, where the functional layer is provided at the winding end of the current collector. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The present invention will be further described below with reference to specific embodiments. It should be understood that these specific embodiments are used to illustrate the present invention and do not limit the scope of the present invention.

[0020] 1. Electrochemical equipment The present invention provides an electrochemical device, the electrochemical device includes an electrode assembly, the electrode assembly includes an electrode piece, the electrode piece includes a current collector, the current collector includes a first region and a second region, an active material layer is provided in the first region, a functional layer is provided in the second region, and when the volume ratio of the functional layer to the volume of the active material layer is R, R satisfies 1%≦R≦10%. The inventor of the present invention has found through research that the liquid retention amount of the electrochemical device can be improved and the cycle characteristics can be improved by coating a functional layer capable of absorbing an electrolyte on the current collector region where the active material of the electrode piece is not coated, and controlling the volume ratio of the functional layer to the volume of the active material layer within the above range. In addition, it is possible to prevent the surface unevenness of the electrochemical device caused by the excess electrolyte being unevenly liberated inside the exterior bag (e.g., aluminum plastic film), and further improve the flatness of the appearance of the electrochemical device, and reduce the loss of energy density. In some embodiments, the functional layer can absorb the electrolyte.

[0021] In the present invention, the "second region" may mean a blank region of the current collector where no active material layer is provided.

[0022] According to some embodiments of the present invention, R may be 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, or 9.5%, or may be in a range consisting of any two of these values. If R is too large, the proportion of the functional layer is too large, and the energy density of the electrochemical device is reduced. If R is too small, the electrolyte retention rate of the functional layer is low, which is disadvantageous for improving the cycle characteristics and appearance of the electrochemical device.

[0023] According to some embodiments of the present invention, the electrochemical device satisfies R≧k / (D×P), where D is the swelling degree of the functional layer, P is the porosity of the active material layer, and k satisfies 0.004≦k≦0.008. In some embodiments, k may be 0.0045, 0.005, 0.0055, 0.006, 0.0065, 0.007, 0.0075, or any value therebetween. The swelling degree of the functional layer and the porosity of the active material layer both affect the absorption of the electrolyte, and generally, the higher the swelling degree and the larger the porosity, the easier it is to absorb more electrolyte, improving the liquid retention capacity of the electrochemical device. However, if the swelling degree is too high and the porosity is too large, the structural stability of the functional layer and the active material layer will be poor, and the volumetric energy density of the electrochemical device will be reduced. As a result of extensive research, the present inventors have found that when the volume ratio and swelling degree of the functional layer and the porosity of the active material layer satisfy the above-mentioned relationship, the electrochemical device simultaneously has excellent cycle characteristics and low energy density loss.

[0024] According to some embodiments of the present invention, when the swelling degree of the functional layer is D, D satisfies 200%≦D≦800%. In some embodiments, the swelling degree of the functional layer may be 220%, 250%, 270%, 320%, 350%, 370%, 390%, 400%, 420%, 450%, 470%, 500%, 520%, 540%, 570%, 600%, 620%, 650%, 670%, 700%, 720%, 750%, or 770%, or may be in a range consisting of any two of these values. If the swelling degree of the functional layer is less than 200%, the electrolyte retention rate of the functional layer is low, which is disadvantageous in improving the appearance of the electrochemical device. If the swelling degree of the functional layer exceeds 800%, the stability of the functional layer itself is poor, and the film is easily peeled off during the cycle process, which further affects the improvement effect of the appearance and the electrical performance of the subsequent cycles. In some embodiments, the swelling degree of the functional layer is 300% to 600%.

[0025] According to some embodiments of the present invention, when the porosity of the active material layer is P, P satisfies 5%≦P≦25%. In some embodiments, P may be 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, or 24%, or a range consisting of any two of these values. The porosity of the active material layer determines the infiltration effect of the electrolyte, and when the porosity is within the above range, the absorption effect of the active material layer on the electrolyte is the highest. If the porosity is too high, the structure of the active material layer becomes unstable and the membrane is easily removed during the cycle process. If the porosity is too low, the absorption speed of the electrolyte is slow, and poor infiltration of the electrolyte is easily caused, and the capacity fade during the charge and discharge process of the electrochemical device is accelerated.

[0026] According to some embodiments of the present invention, the functional layer comprises a polymer formed from at least one of acrylic acid monomers, acrylic ester monomers, and styrene monomers.

[0027] In some embodiments, the acrylic acid monomer comprises at least one of the compounds shown in Formula I:

[0028] [ka]

[0029] where R1 is hydrogen, C1-C 10 Alkyl groups and halogen-substituted C1-C 10 According to some embodiments of the present invention, R1 is selected from C1-C6 alkyl groups and halogen-substituted C1-C6 alkyl groups. In some embodiments of the present invention, R1 is selected from methyl, ethyl, fluorine-containing ethyl, propyl, fluorine-containing propyl, butyl, fluorine-containing butyl, pentyl, and fluorine-containing pentyl groups.

[0030] In some embodiments, the acrylic acid monomers include at least one of acrylic acid, methacrylic acid, and ethyl acrylic acid.

[0031] In some embodiments, the acrylic ester monomer comprises at least one of the compounds shown in formula II:

[0032] [ka]

[0033] where R2 is hydrogen, C1-C 10 Alkyl groups and halogen-substituted C1-C 10 R3 is selected from the group consisting of C1-C 10 Alkyl groups and halogen-substituted C1-C 10 According to some embodiments of the present invention, R2 is selected from hydrogen, C1-C6 alkyl groups, and C1-C6 alkyl groups substituted with halogen. R3 is selected from C1-C6 alkyl groups and C1-C6 alkyl groups substituted with halogen. In some embodiments of the present invention, R2 is selected from hydrogen, methyl, ethyl, and propyl groups. R3 is selected from methyl, ethyl, fluorine-containing ethyl, propyl, fluorine-containing propyl, butyl, fluorine-containing butyl, pentyl, and fluorine-containing pentyl groups.

[0034] In some embodiments, the acrylic ester monomers include at least one of methyl acrylate, methyl methacrylate, ethyl methyl acrylate, ethyl acrylate, ethyl methacrylate, ethyl ethyl acrylate, propyl acrylate, propyl methacrylate, ethyl propyl acrylate, butyl acrylate, butyl methacrylate, ethyl butyl acrylate, pentyl methacrylate, and pentyl acrylate.

[0035] According to some embodiments of the present invention, the styrenic monomer comprises at least one of the compounds shown in formula III:

[0036] [ka]

[0037] Here, n is an integer from 1 to 5, for example, 2, 3, or 4. Each R4 may be the same or different and independently represents hydrogen, C1-C 10 Alkyl groups and halogen-substituted C1-C 10 R5 and R6 may be the same or different and are independently selected from hydrogen, C1-C 10 Alkyl groups and halogen-substituted C1-C 10 According to some embodiments of the present invention, R4 is selected from hydrogen, C1-C6 alkyl groups, and halogen-substituted C1-C6 alkyl groups. R5 and R6 may be the same or different and are independently selected from C1-C 16 In some embodiments of the present invention, R4, R5 and R6 are independently selected from hydrogen, methyl, ethyl and propyl.

[0038] In some embodiments, the styrenic monomers include at least one of styrene, methylstyrene, 2-methylstyrene, 2,4-dimethylstyrene.

[0039] According to some embodiments of the present invention, the raw materials forming the polymer include at least one of a pure acrylic emulsion, a styrene acrylic emulsion, and an acrylate emulsion. In some embodiments, the polymer includes at least one of a pure acrylic emulsion, a styrene acrylic emulsion, and an acrylate emulsion.

[0040] According to some embodiments of the present invention, the raw materials for forming the polymer include a pure acrylic emulsion and a styrene acrylic emulsion. In some embodiments, the mass percentage of the pure acrylic emulsion is 50%-90%, and the mass percentage of the styrene acrylic emulsion is 10%-50%, based on the total mass of the pure acrylic emulsion and the styrene acrylic emulsion.

[0041] According to some embodiments of the present invention, the polymer content, relative to the mass of the functional layer, may be 30% to 100%, for example 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, or 95%, or may be in a range consisting of any two of these values.

[0042] According to some embodiments of the present invention, the functional layer further comprises inorganic particles, which can avoid failure caused by internal short circuit when the electrochemical device is penetrated by external force, and can effectively improve the safety performance of the electrochemical device in the penetration test.

[0043] According to some embodiments of the present invention, the inorganic particles include at least one of boehmite, diaspore, aluminum oxide, barium sulfate, calcium sulfate, and calcium silicate.

[0044] According to some embodiments of the present invention, the electrolyte retention rate of the functional layer is 40% to 120%. In some embodiments, the electrolyte retention rate of the functional layer may be 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100%, 105%, 110%, or 115%, or may be in a range consisting of any two of these values. If the shipping appearance of the electrochemical device meets the requirements, increasing the electrolyte retention rate is advantageous for improving the later cycle stability of the electrochemical device.

[0045] According to some embodiments of the present invention, a non-destructive ultrasonic intelligent diagnostic system is used to measure, and ultrasonic waves are emitted to the electrochemical device along the thickness direction of the electrochemical device, and a signal feedback distribution map for the ultrasonic waves of the electrochemical device is obtained, and the proportion of the area of ​​the electrochemical device in the signal feedback distribution map where the ultrasonic signal intensity is 1333 mV or more is 30% to 95%. Ultrasonic waves are mechanical waves that need to propagate depending on the medium. When there is no electrolyte infiltration between the electrode materials, the propagation of ultrasonic waves is realized only by the direct contact between the electrode material particles, and the irregular particles cause the ultrasonic waves to generate a large amount of reflection and refraction, and the signal intensity is greatly attenuated. However, when the electrolyte can completely infiltrate the electrode material, the liquid environment provides a good propagation path for the ultrasonic waves, and a significant part of the ultrasonic waves is not interfered with by the particles, so that the signal intensity is ensured. Therefore, in the measurement of the non-destructive ultrasonic intelligent diagnostic system, the signal feedback intensity for the ultrasonic waves at each point of the electrochemical device can well characterize the distribution and infiltration situation of the electrolyte inside the electrochemical device, and the higher the proportion of the area with high signal intensity, the more uniform the distribution of the electrolyte inside the electrochemical device.

[0046] According to some embodiments of the present invention, the area ratio of the region where the signal strength is 1333 mV or more may be 35%, 38%, 40%, 45%, 47%, 50%, 53%, 55%, 57%, 60%, 63%, 65%, 67%, 70%, 73%, 75%, 77%, 80%, 83%, 85%, 87%, 90%, 92%, or 94%, or may be in a range consisting of any two of these values. In some embodiments, the area ratio of the region where the signal strength is 1333 mV or more is 50% to 95%.

[0047] According to some embodiments of the present invention, the electrochemical device has a flatness of 0 to 0.5 mm.

[0048] According to some embodiments of the present invention, the electrode assembly is a wound electrode assembly, in which a second region is provided at a winding start end and a winding end end of the current collector, and a functional layer is provided in the second region at the winding end end.

[0049] According to some embodiments of the present invention, the active material layer is a positive electrode active material layer and / or a negative electrode active material layer.

[0050] According to some embodiments of the present invention, the positive electrode active material layer includes a positive electrode active material, a binder, and a conductive agent. In some embodiments, the positive electrode active material may include at least one of lithium cobalt oxide, lithium nickel manganese cobalt oxide, lithium nickel manganese aluminate, lithium iron phosphate, lithium vanadium phosphate, lithium cobalt phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium iron silicate, lithium vanadium silicate, lithium cobalt silicate, lithium manganese silicate, lithium manganese spinel type manganate, lithium nickel manganate spinel type, and lithium titanate. In some embodiments, the binder may include at least one of various adhesive polymers, such as polyvinylidene fluoride, polytetrafluoroethylene, polyolefins, sodium carboxymethylcellulose, lithium carboxymethylcellulose, modified polyvinylidene fluoride, modified SBR rubber, and polyurethane. In some embodiments, any conductive material may be used as the conductive agent as long as it does not cause a chemical change. Examples of the conductive material include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, and carbon fibers; metal-based materials such as metal powders or metal fibers including copper, nickel, aluminum, and silver; conductive polymers such as polyphenylene derivatives, or mixtures thereof.

[0051] According to some embodiments of the present invention, the negative electrode active material layer includes a negative electrode active material, a binder, and a conductive agent. In some embodiments, the negative electrode active material may include a material that reversibly absorbs / releases lithium ions, lithium metal, a lithium metal alloy, or a transition metal oxide. In some embodiments, the negative electrode active material includes at least one of a carbon material or a silicon material, the carbon material includes at least one of graphite and hard carbon, and the silicon material includes at least one of silicon, a silicon oxygen compound, a silicon carbon compound, and a silicon alloy. In some embodiments, the binder includes at least one of styrene butadiene rubber, polyacrylic acid, a polyacrylate, a polyimide, a polyamide imide, polyvinylidene fluoride, polydifluoroethylene, polytetrafluoroethylene, an aqueous acrylic resin, a polyvinyl formal, and a styrene-acrylic acid copolymer resin. In some embodiments, any conductive material may be used as the conductive agent as long as it does not cause a chemical change. In some embodiments, the conductive material comprises at least one of conductive carbon black, acetylene black, carbon nanotubes, ketjen black, conductive graphite, and graphene.

[0052] According to some embodiments of the present invention, the current collector is a positive electrode current collector and / or a negative electrode current collector. In some embodiments, the positive electrode current collector may employ a metal foil strip or a composite current collector. For example, the positive electrode current collector may use an aluminum foil. The composite current collector may be formed by forming a metal material (such as copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy) on a polymer substrate. In some embodiments, the negative electrode current collector may be copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, or a combination thereof.

[0053] The electrode assembly of the present invention further includes a separator, and the material and shape of the separator used in the electrode assembly of the present invention are not particularly limited and may be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or inorganic material formed from a material stable to the electrolyte of the present invention. For example, the separator may include a substrate layer and a surface treatment layer. The substrate layer is a nonwoven fabric, film or composite film having a porous structure, and the material of the substrate layer is at least one selected from polyethylene, polypropylene, polyethylene terephthalate, and polyimide. Specifically, a polypropylene porous membrane, a polyethylene porous membrane, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric, or a polypropylene-polyethylene-polypropylene porous composite membrane can be selected and used.

[0054] A surface treatment layer is provided on at least one surface of the base layer. The surface treatment layer may be a polymer layer or an inorganic layer, or may be a layer formed by mixing a polymer and an inorganic material.

[0055] The inorganic layer includes inorganic particles and a binder, the inorganic particles being at least one selected from aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, and barium sulfate, and the binder being at least one selected from polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylic acid ester, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene, and polyhexafluoropropylene.

[0056] The polymer layer includes a polymer, and the polymer material is at least one selected from polyamide, polyacrylonitrile, acrylic ester polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride, and poly(vinylidene fluoride-hexafluoropropylene).

[0057] The electrochemical device of the present invention further comprises an electrolyte. The electrolyte used in the present invention may be any electrolyte known in the art.

[0058] In some embodiments, the electrolyte comprises an organic solvent, a lithium salt, and an optional additive. The organic solvent of the electrolyte according to the present invention may be any organic solvent known in the prior art that is used as a solvent for electrolytes. The electrolyte used in the electrolyte according to the present invention is not particularly limited and may be any electrolyte known in the prior art. The additive of the electrolyte according to the present invention may be any additive known in the prior art that is used as an additive for electrolytes. In some embodiments, the organic solvent includes, but is not limited to, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), propylene carbonate, or ethyl propionate. In some embodiments, the organic solvent includes an ether solvent, such as at least one of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME). In some embodiments, the lithium salt includes at least one of an organic lithium salt and an inorganic lithium salt. In some embodiments, the lithium salt includes, but is not limited to, lithium hexafluorophosphate (LiPF), lithium tetrafluoroborate (LiBF), lithium difluorophosphate (LiPO2F2), lithium bis(trifluoromethanesulfonyl)imide LiN(CF3SO2)2 (LiTFSI), lithium bis(fluorosulfonyl)imide Li(N(SO2F)2) (LiFSI), lithium bis(oxalato)borate LiB(C2O4)2 (LiBOB), or lithium difluoro(oxalato)borate LiBF2(C2O4) (LiDFOB).

[0059] In some embodiments, the electrochemical device of the present invention includes, but is not limited to, any type of primary battery, secondary battery, or capacitor. In some embodiments, the electrochemical device is a lithium secondary battery. In some embodiments, the lithium secondary battery includes, but is not limited to, a lithium metal secondary battery, a lithium ion secondary battery, a sodium ion secondary battery, a lithium polymer secondary battery, or a lithium ion polymer secondary battery.

[0060] 2.Electronic equipment The present invention further provides an electronic device comprising an electrochemical device according to the first aspect of the present invention.

[0061] The electronic equipment or device of the present invention is not particularly limited. In some embodiments, the electronic equipment of the present invention includes, but is not limited to, notebook computers, pen-input computers, mobile computers, electronic book players, mobile phones, portable facsimiles, portable copy machines, portable printers, stereo headsets, video recorders, liquid crystal televisions, portable cleaners, portable CD players, mini discs, transceivers, electronic notebooks, calculators, memory cards, portable tape recorders, radios, backup power sources, motors, automobiles, motorcycles, power-assisted bicycles, bicycles, lighting equipment, toys, game consoles, clocks, power tools, strobes, cameras, large household storage batteries, and capacitors.

[0062] In the following examples and comparative examples, reagents, materials and equipment used are commercially available unless otherwise stated.

[0063] Examples and Comparative Examples

[0064] Preparation of functional layer slurry: The binder (see the table below for the specific composition), any inorganic particles (see the table below for the specific composition), and solvent were mixed uniformly to prepare a slurry. The viscosity of the slurry must be controlled to 200-3000 mPa·S and the solid content to 35%-50%. Here, the solvent is selected according to the type of binder. If the binder is aqueous, an aqueous solvent (e.g., deionized water, etc.) can be selected, and if the binder is oil-based, an oil-based solvent (e.g., N-methylpyrrolidone, etc.) can be selected.

[0065] Preparation of electrode pieces: The slurry prepared above was applied to the target area of ​​the current collector (the winding end of the current collector as shown in Figure 2), and the solvent was dried to obtain an electrode piece coated with a functional layer. A slurry containing an active material was applied to the area not coated with the functional layer, and the electrode piece was obtained through further drying and roll pressing.

[0066] Here, the slurry containing the active material is a positive electrode active material slurry or a negative electrode active material slurry. Specifically, the positive electrode active material slurry is a slurry prepared by mixing lithium cobalt oxide, conductive carbon, and polyvinylidene fluoride in a mass ratio of 96:2:2, and adding N-methyl-2-pyrrolidone (NMP). The negative electrode active material slurry is a slurry prepared by mixing graphite, styrene butadiene rubber, and sodium carboxymethylcellulose in a mass ratio of 98:1:1, and adding deionized water.

[0067] Preparation of secondary battery: The positive electrode, separator (PE porous polymer film), and negative electrode are stacked in order, and the separator is placed between the positive electrode and the negative electrode to serve as an insulator, and then wound up to obtain an electrode assembly. The electrode assembly is placed in an exterior aluminum plastic film, and electrolyte (a solution in which the solvent is EC and DMC in a volume ratio of 1:1, and the mass concentration of LiPF6 is 12.5% ​​relative to the mass of the electrolyte) is injected, and the secondary battery is prepared through processes such as vacuum sealing, standing, formation, and shaping.

[0068] Measurement method 1. Volume ratio of functional layer to active material layer The pole piece coated with the functional layer was removed from the secondary battery in an atmosphere of (25±3)°C. It was then placed in an oven at 85°C to dry, and the width a and length b of the active material layer, and the width A and length B of the functional layer were measured with a soft ruler. Furthermore, the thickness h of the active layer material and the layer thickness H of the functional layer were measured with a CCD detector. The ratio R of the volume of the functional layer / the volume of the active material layer was (A×B×H) / (a×b×h)×100%.

[0069] 2. Porosity of active material layer The porosity of the active material layer was measured using a mercury porosimeter (model number V9600), and the specific measurement steps were as follows.

[0070] a.Positive and negative pole pieces are 15.4025cm 2 If the conditions for pressing into a circular piece were not met, the piece was cut into a rectangle of 4.0 cm x 3.2 cm with a blade, the area was recorded, the thickness was measured with a micrometer, and the piece was weighed on an analytical balance, after which the data was recorded in the measurement record sheet.

[0071] b. The positive and negative electrodes were cut into smaller pieces, wrapped in cotton swabs, and inserted into a sample tube for measurement. After clamping the sample tube, it was inserted into "station 1" on the right side of the low-pressure station, and then a metal sleeve and electrode were attached.

[0072] c.Enter the low pressure interface, click Operations on the software toolbar, click Low Pressure Analysis on the drop-down menu, select Station1 (or Station2), click OK, and enter the low pressure operation interface. Enter the sample information in the low pressure operation interface, set the sample specifications, capacitance constant, and evacuation program, click Run Mode to select Evacuate and fill only mode, then click OK, confirm that the information is correct, and click Start to start low pressure mercury filling.

[0073] d. After the low pressure mercury filling was completed, the electrode and metal sleeve were removed and the sample tube was taken out of the low pressure station to check whether there were any air bubbles in the mercury filling and whether it was completely filled.

[0074] e. Install the metal protective sleeve on the sample tube and slowly place it into the high pressure chamber, click Operations on the software toolbar, select High Pressure Analysis from the drop-down menu, enter the high pressure software operation interface, enter the sample ID, Comments, and Sample Weight information of the sample, other parameter setting details refer to the general parameter setting table, enter the Run Mode interface to set the relevant parameters, click OK, confirm that the information is correct, click Start to start, and the file was automatically saved after the analysis was completed. Editing raw data: Click the right button of the mouse to select select all, then click the right button again to select copy to copy the results into an EXCEL table, and use the "NPDDrawPlot" macro to create a pore size distribution diagram and a porosity diagram, and set the compressed density to the actual measured value.

[0075] 3. Ultrasonic measurement Using non-destructive ultrasonic intelligent diagnostic equipment (model: UBSC-LD), ultrasonic waves (50MHZ, 400mV) were emitted to the secondary battery along the thickness direction of the secondary battery, and a signal feedback distribution map for the ultrasonic waves at each point of the battery was obtained. Using integration software, such as JMP software, in the signal feedback distribution map, the total area where the battery was measured is S, the area of ​​the area where the signal strength is ≧1333mV is S1, and the proportion of the area where the signal strength is ≧1333mV is S1 / S×100%.

[0076] 4, Electrolyte retention rate a) In an atmosphere of (25±3)℃, the pole piece coated with the functional layer was taken out from the secondary battery. If there was another coating layer on the other side of the current collector coated with the functional layer, it should be physically or chemically removed so as not to damage the functional layer. Then, the current collector coated with the functional layer was cut with a cutting machine.

[0077] b) Each of the cut current collectors (including the current collector) coated with the functional layer was weighed at least three times using an electronic balance, and the weights were recorded as m1, m2, m3, etc., and the average value m was calculated.

[0078] c) The current collector (including the current collector) on which the functional layer was applied after the above weighing was placed in an oven at 85°C and dried for 30 to 60 minutes. After confirming that all of the electrolyte inside the functional layer was dry, the weight of the current collector on which the functional layer was applied after drying was then weighed again at least three times and these were recorded as M1; M2; M3... and the average weight M was calculated.

[0079] d) The functional layer was removed by a physical or chemical method without damaging the corresponding current collector, and the weight of the corresponding current collector was weighed at least three times, which were respectively noted as G1; G2; G3…, and the average weight G was calculated.

[0080] e) The electrolyte retention rate of the functional layer is R=(mM) / (MG)×100%.

[0081] 5. Swelling degree a) Preparation of adhesive film: In an atmosphere of (25±3) ° C, the pole piece coated with the functional layer was removed from the secondary battery. If there is another coating layer on the other side of the current collector coated with the functional layer, it must be physically or chemically removed so as not to damage the functional layer. Next, the current collector coated with the functional layer was cut with a cutting machine, immersed in dimethyl carbonate DMC to remove the electrolyte dissolved in the functional layer, the current collector was removed and dried, and then placed in water to dissolve the functional layer and form an aqueous solution. The aqueous solution was poured into the adhesive film preparation mold, and if there were any air bubbles, they were pulled up and removed. The mold was placed in a 60 ° C oven for 12 h, and after baking, the appearance and hardness of the adhesive film were observed. If it was not completely dry, the baking was continued until it was dry.

[0082] b) The prepared adhesive film was cut into strips with scissors.

[0083] c) The strip of adhesive film was weighed and the initial weight a was recorded. It was placed in a vial and electrolyte (a solution of 12.5% ​​LiPF6 by mass concentration relative to the mass of the electrolyte, with the solvent being EC and DMC in a volume ratio of 1:1) was added so that the adhesive film was 2-3 cm thick. The vial was then sealed and placed in a vacuum drying oven at 85°C for 6 h.

[0084] d) Measurement of the swelling degree of the adhesive film: The adhesive film was taken out and wiped clean with dust-free paper, and the adhesive film weight b at this time was recorded. Swelling degree=(ba) / a×100%. Three samples were prepared for parallel testing, and the swelling degrees obtained were arithmetically averaged to obtain the swelling degree of the functional layer.

[0085] 6, flatness The flatness of the secondary battery was measured using a laser scanning method. Specifically, an optical instrument was used to scan the entire outline of the secondary battery, and then a 3D model was made, and then the difference between the overall thickness value and the cross-sectional thickness value was calculated and recorded as P. The difference is the flatness of the secondary battery. If P≦0.5mm, the flatness of the secondary battery is OK and meets the requirement. If P>0.5mm, the flatness is NG and does not meet the requirement.

[0086] 7. Nail penetration pass rate The secondary battery to be measured was charged at a constant current of 0.05C up to the design full charge voltage, and then charged at the design full charge voltage until the current reached 0.025C (cut-off current), and the secondary battery was fully charged. The appearance of the secondary battery before measurement was recorded. A nail penetration measurement was performed on the battery in an environment of 25±3°C, with the steel nail having a diameter of 4mm and a penetration speed of 30mm / s, and the nail penetration position being located at the geometric center of the secondary battery. The measurement was performed for 3.5 minutes or stopped after the surface temperature of the electrode assembly had dropped to 50°C. Ten secondary batteries were used as a set, and the condition of the secondary batteries during the measurement was observed. The pass criterion was that the secondary batteries did not burn or explode.

[0087] 8. 25℃ / 45℃ cycle capacity retention rate The cycle characteristics were measured using a Land CT2001A under an atmosphere of 25°C / 45°C (±3°C). The secondary battery was first charged at a constant current of 0.2C to 4.45V, then charged at a constant voltage of 4.45V until the current was less than 50μA. It was then discharged at a constant current of 0.2C to 3.0V, and the discharge capacity of the first cycle was recorded and designated as the initial capacity C0. The above charge / discharge cycle was repeated 500 times, and the discharge capacity of the 500th cycle was recorded and designated as C500. The capacity retention rate at the 500th cycle = C500 / C0 x 100%.

[0088] Measurement results

[0089] [Table 1]

[0090] Note: In each example in Table 1, in the slurry forming the functional layer, the binder is a pure acrylic emulsion, the inorganic particles are boehmite, the ratio of the mass of the pure acrylic emulsion to the mass of the boehmite is 34:3, the swelling degree D of the functional layer is 550%, and the porosity P of the active material layer is 15%. As can be seen from the data in Table 1, within a certain range, the larger the ratio R of the volume of the functional layer to the volume of the active material layer, the higher the electrolyte retention rate of the functional layer, which in turn improves the capacity retention rate and safety performance, and also improves the flatness of the appearance.

[0091] [Table 2]

[0092] Note: In each example in Table 2, in the slurry forming the functional layer, the percentages of each component of the binder are all mass fractions, the inorganic particles are boehmite, the ratio of the mass of the binder to the mass of the boehmite is 34:3, k is 0.008, and the porosity P of the active material layer is 15%. As can be seen from the data in Table 2, the components of the binder directly affect the swelling degree, which in turn affects the electrolyte retention rate and the proportion of the wave number region of ≥ 1333 mV. When the stability of the functional layer can be ensured, the greater the swelling degree, the greater the electrolyte retention rate and the proportion of the wave number region of ≥ 1333 mV, and the better the corresponding battery capacity retention rate.

[0093] [Table 3]

[0094] Note: In each example in Table 3, in the slurry forming the functional layer, the binder is a pure acrylic emulsion, the inorganic particles are boehmite, the ratio of the mass of the pure acrylic emulsion to the mass of the boehmite is 34:3, the swelling degree D of the functional layer is 550%, and k is 0.008. As can be seen from the data in Table 3, the porosity of the active material layer affects the effect of the functional layer in the secondary battery. When the porosity is within a certain range (4% to 18%) and P is increased, the infiltration of the electrolyte is better, the cycle capacity retention rate is improved accordingly, and the flatness becomes better.

[0095] [Table 4]

[0096] Note: In each example in Table 4, in the slurry forming the functional layer, the binder is a pure acrylic emulsion, the ratio of the mass of the pure acrylic emulsion to the mass of the boehmite is 34:3, the swelling degree D of the functional layer is 550%, the porosity P of the active material layer is 15%, and k is 0.008. As can be seen from the data in Table 4, the type of inorganic particles affects the safety performance of the secondary battery mainly because different types of inorganic particles have different morphologies, which affect the appearance (e.g., flatness) of the coating layer, thereby affecting the safety performance of the battery. In the above-mentioned examples, the secondary battery using boehmite has excellent safety performance.

[0097] Although illustrative embodiments have been disclosed and described, those skilled in the art should understand that the above-described embodiments should not be construed as limiting the present invention, and that the embodiments can be modified, substituted, and altered without departing from the spirit, principle, and scope of the present invention.

Claims

1. 1. An electrochemical device comprising: an electrode assembly; The electrode assembly includes an electrode piece, The electrode piece includes a current collector, the current collector includes a first region and a second region; an active material layer is provided in the first region; A functional layer is provided in the second region, An electrochemical device, wherein R is a ratio of the volume of the functional layer to the volume of the active material layer, and R satisfies 1%≦R≦10%.

2. The electrochemical device satisfies R≧k / (D×P), 2. The electrochemical device according to claim 1, wherein D is the swelling degree of the functional layer, P is the porosity of the active material layer, and k satisfies 0.004≦k≦0.

008.

3. The electrochemical device according to claim 1 , wherein the swelling degree of the functional layer is defined as D, and D satisfies 200%≦D≦800%.

4. 2. The electrochemical device according to claim 1, wherein P is a porosity of the active material layer, and P satisfies 5%≦P≦25%.

5. 10. The electrochemical device of claim 1, wherein the functional layer comprises a polymer formed from at least one of an acrylic acid monomer, an acrylic ester monomer, and a styrene monomer.

6. The electrochemical device according to claim 5 , wherein the mass percentage of the polymer is 30% to 100% with respect to the mass of the functional layer.

7. The functional layer further contains inorganic particles, 6. The electrochemical device of claim 5, wherein the inorganic particles include at least one of boehmite, diaspore, aluminum oxide, barium sulfate, calcium sulfate, and calcium silicate.

8. The electrochemical device comprises: (a) the electrolyte retention rate of the functional layer is 40% to 120%; (b) using a non-destructive ultrasonic intelligent diagnostic system to measure, emit ultrasonic waves to the electrochemical device along the thickness direction of the electrochemical device, obtain a signal feedback distribution map of the electrochemical device for the ultrasonic waves, and the proportion of the area of ​​the electrochemical device in the signal feedback distribution map where the ultrasonic signal intensity is 1333 mV or more is 30% to 95%; (c) the flatness of the electrochemical device is 0 to 0.5 mm; The electrochemical device according to claim 1 , wherein at least one of the above is satisfied.

9. The electrochemical device according to claim 1 , wherein the electrode assembly is a wound electrode assembly, the second region is provided at a winding start end and a winding end end of the current collector, and the functional layer is provided in the second region at the winding end end.

10. An electronic device comprising an electrochemical device according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Lithium ion battery negative electrode polymer protective coating, and preparation method and application thereof

    CN111647345A

  • Negative electrode complex with high cycle performance, preparation method of negative electrode complex and lithium metal battery

    CN113488616A

  • Pole piece, secondary battery and electronic device

    CN113826242A

  • Electrode assembly having insulating film formed on tab, method for manufacturing same, and lithium secondary battery comprising same

    CN114128035A

  • Electrochemical device and electronic device

    CN114175306A